Classical and Paradoxical Effects of TNF-α on Bone Homeostasis - Osta, Bilal; Benedetti, Giulia; Miossec, Pierre (Frontiers in Immunology, 2014)
TNF-α plays an essential role in the regulation of bone homeostasis in several chronic immune and inflammatory joint diseases, where inhibition of TNF has led to significant clinical improvement. However, TNF-activated pathways and mechanisms involved in bone remodeling remain unclear. So far, TNF-α was known as an inhibitor of osteoblast differentiation and an activator of osteoclastogenesis. Recent contradictory findings indicated that TNF-α can also activate osteoblastogenesis. The paradoxical role of TNF-α in bone homeostasis seems to depend on the concentration and cell type used as well as on the exposure time. This review aims to summarize the recent contradictory findings on the regulation of bone homeostasis by TNF-α at the isolated cell, whole bone, and whole body levels. In addition, the involvement of TNF-α in the bone remodeling imbalance is observed in inflammatory joint diseases including rheumatoid arthritis and ankylosing spondylitis which are associated with bone destruction and ectopic calcified matrix formation, respectively. Both diseases are associated with systemic / vertebral osteoporosis.